UPLC-Q-TOF/MS-based metabolomics reveals modulatory effects of Mesona chinensis Benth polysaccharide in liver injury mice induced by cyclophosphamide - Yuzhen Hong; Mingyue Shen; Qiang Yu; Yi Chen; Jianhua Xie (Food Science and Human Wellness)
The main purpose of this study was to investigate the improvement effect of Mesona chinensis Benth polysaccharide (MP) on cyclophosphamide (CTX) induced liver injury in mice. To explore metabolic profile of liver tissue and feces among normal group, CTX-induced group and MP management group based on metabolomics method by using UPLC-Q-TOF/MS. The results showed that MP could alleviate liver injury and promote the production of short chain fatty acids (SCFAs), with the best dose of 200 mg/kg·body weight (bw). The principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (OPLS-DA) scores plots of the liver and feces samples showed a clear separation among normal, model and high-dose of MP (MPH). There were 18 endogenous metabolites in liver and 29 endogenous metabolites in feces, which were mainly involved in 8 metabolic pathways: taurine and hypotaurine metabolism, phenylalanine metabolism, α-linolenic acid metabolism, tricarboxylic acid (TCA) cycle, phenylalanine, tyrosine and tryptophan biosynthesis, arachidonic acid metabolism, sphingolipid metabolism as well as tryptophan metabolism. Moreover, a common metabolite arachidonic acid was observed in liver and feces samples. These endogenous metabolites may be considered to be MP's response to liver protection. It will help to further understand the mechanism of MP and provide a basis for further research.